2010
DOI: 10.1111/j.1553-2712.2009.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Bedside Ultrasound and Supine Anteroposterior Chest Radiographs for the Identification of Pneumothorax After Blunt Trauma

Abstract: Objectives: Supine anteroposterior (AP) chest radiographs in patients with blunt trauma have poor sensitivity for the identification of pneumothorax. Ultrasound (US) has been proposed as an alternative screening test for pneumothorax in this population. The authors conducted an evidence-based review of the medical literature to compare sensitivity of bedside US and AP chest radiographs in identifying pneumothorax after blunt trauma.Methods: MEDLINE and EMBASE databases were searched for trials from 1965 throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
2
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(138 citation statements)
references
References 26 publications
(27 reference statements)
2
121
2
13
Order By: Relevance
“…11 EPs have become more adept at fracture diagnosis through independent review of US and radiographic imaging, and many researchers have examined the ability of EPs to obtain US imaging and diagnose fracture. 12,13 Additionally, bedside US has excellent diagnostic test characteristics when performed by EPs compared to radiologists in the diagnostic evaluation for soft tissue infections, 14 cholecystitis, 15 pneumothorax, 16 or ruling out ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…11 EPs have become more adept at fracture diagnosis through independent review of US and radiographic imaging, and many researchers have examined the ability of EPs to obtain US imaging and diagnose fracture. 12,13 Additionally, bedside US has excellent diagnostic test characteristics when performed by EPs compared to radiologists in the diagnostic evaluation for soft tissue infections, 14 cholecystitis, 15 pneumothorax, 16 or ruling out ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Bilgisayarlı tomografi (BT), karıniçi yaralanma ve pnömotoraks saptanmasında, altın standart olmakla birlikte, son yıllarda yapılan çalışmalarla, acil servis hastalarında pnömotoraks değerlendirmesinde, USG'nin duyarlı-lığının yüksek olduğu bilinmektedir. [7][8][9][10][11] Küçük boyutlu olanları, konservatif olarak tedavi edilebilse de, bir çoklu travma hastasında operasyon esnasında veya sonrasında, uygulanacak pozitif basınçlı ventilasyon, pnömotoraksın, tüp torakostomi (TT) gereksinimi yaratabilecek boyutlara veya tansiyon pnömotoraksa dönüşmesine sebep olabilir. Bu yüzden hangi boyutta olursa olsun pnömotoraks varlığının bilinmesi önem-lidir.…”
Section: Sonuçunclassified
“…However, the American College of Emergency Physicians' guides indicate that at least 25-50 chest US examinations are required to gain competence in this field. [13] In our study, all physicians were trained to use chest US for PNX diagnosis and each had already performed minimum 150 chest US examinations before our study. It is accepted that the effectiveness of US would increase if US is performed and interpreted by the physician who examines the patient.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Several studies have indicated that US has higher sensitivity and selectivity than direct radiography for the detection of PNX, [3,[9][10][11] and the reliability of US has been confirmed by CT in some series. [12] The number of studies, which concentrate only on the detection of PNX by chest US performed by emergency physicians in blunt thoracic trauma (BTT) patients, is low, [13] and the group of patients in these studies is also small. The current study was designed considering the need for more comprehensive studies in the field.…”
Section: Introductionmentioning
confidence: 99%